IL-6 deletion decreased REV-ERBα protein and influenced autophagy and mitochondrial markers in the skeletal muscle after acute exercise - Pinto, Ana P.; Muñoz, Vitor R.; da Rocha, Alisson L.; Rovina, Rafael L.; Ferrari, Gustavo D.; Alberici, Luciane C.; Simabuco, Fernando M.; Teixeira, Giovana R.; Pauli, José R.; de Moura, Leandro P.; Cintra, Dennys E.; Ropelle, Eduardo R.; et al. (Frontiers in Immunology, 2022)
Interleukin 6 (IL-6) acts as a pro and anti-inflammatory cytokine, has an intense correlation with exercise intensity, and activates various pathways such as autophagy and mitochondrial unfolded protein response. Also, IL-6 is interconnected to circadian clock-related inflammation and can be suppressed by the nuclear receptor subfamily 1, group D, member 1 (Nr1d1, protein product REV-ERBα). Since IL-6 is linked to physical exercise-modulated metabolic pathways such as autophagy and mitochondrial metabolism, we investigated the relationship of IL-6 with REV-ERBα in the adaptations of these molecular pathways in response to acute intense physical exercise in skeletal muscle. The present study was divided into three experiments. In the first one, wild-type (WT) and IL-6 knockout (IL-6 KO) mice were divided into three groups: Basal time (Basal; sacrificed before the acute exercise), 1 hour (1hr post-Ex; sacrificed 1 hour after the acute exercise), and 3 hours (3hr post-Ex; sacrificed 3 hours after the acute exercise). In the second experiment, C2C12 cells received IL-6 physiological concentrations or REV-ERBα agonist, SR9009. In the last experiment, WT mice received SR9009 injections. After the protocols, the gastrocnemius muscle or the cells were collected for reverse transcription-quantitative polymerase chain reaction (RTq-PCR) and immunoblotting techniques. In summary, the downregulation of REV-ERBα, autophagic flux, and most mitochondrial genes was verified in the IL-6 KO mice independent of exercise. C2C12 cells receiving IL-6 did not modulate the Nr1d1 mRNA levels but upregulated the expression of some mitochondrial genes. However, when treated with SR9009, IL-6 and mitochondrial genes expression were upregulated in C2C12 cells. The WT treated with SR9009 showed an upregulation of autophagic genes. In conclusion, the present study verified that the adaptations required through physical exercise (increases in mitochondrial content e improvement of autophagy machinery) might be intermediated by an interaction between IL-6 and REVERB𝛼.